Factores sociodemográficos, culturales y su relación con el conocimiento en bioseguridad en trabajadores de la Ipress I-4 Moronacocha, Iquitos 2021 - Rengifo Tunjar, Herla Julia (2023)
The objective was to determine the relationship that exists between sociodemographic and cultural factors with the level of knowledge in biosafety in the workers of the IPRESS I-4 Moronacocha, 2021. The study was quantitative and had a non-experimental, descriptive, correlational, prospective and transversal design. The population and sample were made up of 129 health and administrative personnel from the IPRESS, non-probabilistic convenience sampling was used, with the sample being 129 workers, the survey was used as a technique and the questionnaire as an instrument. SPSS v23 software was used for data analysis. Obtaining the following results: regarding socio-demographic and cultural factors, 93% were 23 to 60 years old and 7% were 61 to 71 years old, in terms of sex, 68.2% were female and 31.8% were female. % male sex. Place of origin, 87.6% are from urban origin, 10.1% urban – marginal and 2.3% rural. Educational level, with 51.2% university education, 47.3% technical education and 1.6% secondary education. The level of knowledge about biosafety, 63.5% had a good to excellent level and 36.5% had a poor to average level. It is concluded that there is a relationship between sociodemographic and cultural factors and the level of knowledge in biosafety in the workers of the IPRESS I-4 Moronacocha, 2021, age p=0.04, level of education p= 0.023, profession p= 0.007 no relationship was found with sex p= 0.074 and place of origin p= 0.587.